Geology and Structural Geology at Kg. Gajah, Perak - Ahmad, Bahauddin (2016)
This final year project discussed primarily on the geology and structural geology of Kg. Gajah which is located at the southern part of Kati Formation. The present work on the Kg. Gajah outcrop is not based on previous project and research. However, previous studies on the Kati formation is used as reference and guidance. Kg. Gajah has a distinct topographic unit which consists of an interbedded sequence of sandstone and mudstone/shale trending North-West to South-East. A total of four outcrops were investigated in detail. Most of the area exposed to high weathering and mostly covered with lateritic soil (iron oxide). During the fieldwork, the determination of the bedding orientation in term of strike and dip and sedimentary logging were carried out and recorded in systematic way to study geology and structural style, respectively. Rock samples from each outcrop were collected to perform lab experiments such as thin section and SEM for mineral identification. All of these outcrops are from the same origin but due to the forces that acted on this area had caused few changes especially the dipping angle so structural analysis is the best way to specify the direction of deformation. For the structural analysis, based on the stereonet, the maximum stress (σ1) is from Northeast-Southwest direction while the folding axis lies on Northwest-Southeast direction. Thus, the trend of the dip of beds is in NW-SE direction. This correspond to the general trend of folding in regional context which is in NW-SE direction. The present of sedimentary structures also act as evidence in predicting the depositional environment of this area. The less burrow tracks found in the area shows that the depositional environment would be a shallow marine environment where the water tides are effecting the shallower environment which prevent the organism to exist. The final outcome to this project is mainly to produce a detailed geological map of Kg. Gajah by considering both lithological and structural geology.